PENGARUH PERILAKU CYBERBULLYING DI INSTAGRAM TERHADAP KONSEP DIRI GENERASI Z - Maria Ulfa (2021)
Instagram is the one of the social media that is widely used by users to share their daily activities. Various impacts can result from the use of Instagram. One of them is cyberbullying behavior. And Generation Z is one of the populations that currently use Instagram a lot. And from the research that has been described previously, cyberbullying behavior is the cause of the emergence of a negative self-concept. Meanwhile, self-concept has an important influence on the life of Generation Z. The purpose of this study is to identify how much cyberbullying behavior on Instagram affects self-concept in Generation Z. The theory used is the uses and effect theory. The research method used in this research is explanative quantitative method. The results of the correlation test revealed that cyberbullying behavior (X) and self-concept (Y) had a moderate relationship level of 0.513. The results of the coefficient of determination test revealed that the contribution of cyberbullying behavior (X) to self-concept (Y) was 26.3%. And the remaining 73.7% is influenced by other factors.